Penyuluhan Dampak Sampah Terbuka Bagi Kesehatan - Situngkir, Decy; Nitami, Mayumi (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
One of waste management is not to leave the trash open. Itcan cause health problems for us. This counseling aims to provide an understanding of the impact of open waste on health. Counseling is carried out face-to-face while still implementing health protocols, for ± 50 minutes. The extension media uses power points and posters. Before and after the counseling, an initial test and a final test were carried out through a questionnaire to determine the knowledge of the residents of RW 08. As a result, participants knew the types of diseases from waste left open (from 83% to 100%), knew the impact of open waste on the environment (from 90% to 100%). 97%), direct impact if waste is left open (from 37% to 100%), indirect impact if waste is left open (from 70% to 100%), how to properly sort waste (from 75% to 96%), knowing classification of plastic and cans waste (from 70% to 93%), knowing behaviors that can cause disease due to open waste (from 93% to 100%), knowing the benefits of protecting the environment from open waste (from 90% to 100%), knowing management good waste so as not to pollute and damage the environment (from 100% to 100%). Based on this, it is concluded that there is an increase in their knowledge about the impact of open waste on health